Peran Guru sebagai Pembimbing Rohani dalam Pendidikan Agama Kristen di Era Digital - Krisalin Melodia; Putri Prameswari; Febri Pamungkas (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
The digital era brings new challenges for Christian religious education, especially in the role of teachers as spiritual guides. This article highlights the important role of teachers in accompanying students to understand and live the Christian faith amidst the rapid flow of information. This study uses qualitative methods through interviews and observations of Christian religious education teachers. The results show that the use of digital technology can be an effective tool when combined with a personal pastoral approach. This article provides recommendations for strategies to strengthen the role of teachers in the digital era.